2018
DOI: 10.7903/cmr.18086
|View full text |Cite
|
Sign up to set email alerts
|

Exploring The Social Marketing Impacts of Virtual Brand Community Engagement

Abstract: The number of people using online communities is rising. The study found that more consumers find and evaluate goods through social media networks. At the same time, marketers continue to promote brand recognition, but more importantly, to increase user engagement. However, the link between the brand community and social media has become the focus of the marketing staff and the public. But the academic research of the brand community and the social media in the past focused on brand loyalty. Thus, the aim of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 31 publications
1
11
0
Order By: Relevance
“…H2 -SMM impacts on the brand awareness (BA) of micro-learning-platform students H3 -CBE impacts on the brand awareness (BA) of micro-learning-platform students At the same time, previous research has shown that CBE can act as a mediator between SMM and BA, as proposed by Bruhn et al [71] and Chokpitakkul & Anantachart [120], or between SMM and brand equity as confirmed by Chiang et al [121]. In this sense it is likely that this mediating effect also occurs in the micro-learning platform sector, and therefore the following hypothesis is proposed: H4 -CBE is a mediator between SMM and BA in micro-learning platform students…”
Section: Brand Awarenessmentioning
confidence: 86%
“…H2 -SMM impacts on the brand awareness (BA) of micro-learning-platform students H3 -CBE impacts on the brand awareness (BA) of micro-learning-platform students At the same time, previous research has shown that CBE can act as a mediator between SMM and BA, as proposed by Bruhn et al [71] and Chokpitakkul & Anantachart [120], or between SMM and brand equity as confirmed by Chiang et al [121]. In this sense it is likely that this mediating effect also occurs in the micro-learning platform sector, and therefore the following hypothesis is proposed: H4 -CBE is a mediator between SMM and BA in micro-learning platform students…”
Section: Brand Awarenessmentioning
confidence: 86%
“…SOVC develops a unification among community members (Yao et al, 2021) and incorporates a significant role in predicting consumer behavior in C2C communities. It motivates the members to make the transaction with a specific brand (Chiang et al, 2018); brand trust is the other most vital determinant in online shopping. The influence of SOVC reflects the buying pattern of consumers (González-Anta et al, 2021); the brand's image dictates the trade, as the feedback established for a seller will either boost or knock down the sales, dependent upon the reviews from the buyers of the community.…”
Section: Sense Of Virtual Community and Brand Trustmentioning
confidence: 99%
“…In this context, we consider sharing, in terms of the extent of involvement, as the highest form of engagement followed by commenting and liking (Bitiktas et al, 2020;Cho et al, 2014;Cooper et al, 2019;Swani et al, 2014). Higher active or passive customer participation (customer engagement) with contents at least leads to better spreading the company messages, create better customer experience (Chiang et al, 2018), by enhancing relationships (De Vries et al, 2014), and increasing customers' value (Ersoy et al, 2018). For coffee-shops, social networks are a particularly valuable reference for customers when choosing a venue (E. Kim et al, 2016) because of the intangibility of their services.…”
Section: Short Theoretical Backgroundmentioning
confidence: 99%